Pagamento por serviços ambientais como instrumento econômico de incentivo à proteção das áreas de reserva legal - Vicente, Laura Lícia de Mendonça (2012)
This paper aims to discuss the possibility of establishment of public schemes of payments for environmental services to rural producers who recover and preserve the legal reserve areas within their properties. That s because, even if imposed by law, this positive obligation, whose costs are assigned exclusively to rural producers, generates positive environmental externalities that are freely enjoyed by the whole society. In our view, this equation must find a new equilibrium point, forming a just distribution of benefits and costs of environmental preservation. In this approach, we consider the Payment for Environmental Services PES mechanism an important economic instrument capable of inducing socially desirable behaviors, effectively ensuring the protection of the legal reserve areas, and allowing at the same time, an increase in the producer s income. Our understanding is supported in the protector-receiver principle, which houses the idea of the internalizations of positive externalities as a way to balance economic relationship among the stakeholders (providers and beneficiaries)